Modelling of N-carboxy anhydride copolymerisations for improved sequence control of poly(amino acid)s in bioengineering applications - Zelzer, Mischa (2022)
Synthetically manufactured poly(amino acid)s have been exploited in a variety of bioengineering applications including antimicrobial surfaces and cell culture substrates because of their ability to display functionality linked to secondary structure formation. This functionality is closely connected to the sequence of the amino acids in the poly(amino acid) chains. N-carboxy anhydride (NCA) polymerisation is an attractive route to manufacture poly(amino acid)s but it lacks sequence control. Furthermore, experimental sequence analysis of poly(amino acid)s is challenging. Computational methods are an attractive alternative to obtain sequence related information but few computational copolymerisation models exist for this purpose and none have been designed for NCA polymerisations.